Making the best use of experts' estimates to prioritise monitoring and management actions: A freshwater case study. (1st June 2018) - Nicol, Sam; Ward, Keith; Stratford, Danial; Joehnk, Klaus D.; Chadès, Iadine
Abstract: Under limited time and resources, ecological managers are under increasing pressure to demonstrate tangible impact of monitoring activities. Value of Information (VOI) has been advocated as an ideal tool to evaluate whether more data is required to improve expected management outcomes. Yet, despite several recent works explaining its value, VOI remains seldom used in practice. Here we provide an example of a successful ecological application of VOI. We apply VOI to a novel multi-objective freshwater management problem and show how to make the best use of expert data through a robust sensitivity analysis. Unlike previous VOI approaches, our analysis provides statistical confidence to our recommendations. We apply our approach to the recovery of Moira grass ( Pseudoraphis spinescens ) plains, a threatened vegetation community at the Ramsar-listed Barmah Forest on the Murray River, Australia. Working closely with managers, we discovered that although many threats may impede Moira grass recovery, reducing grazing pressure and applying ideal depth and duration of flooding were most likely to lead to recovery. We found that learning from monitoring can significantly increase the existing extent of Moira grass, although these gains are modest compared to immediate management action. Our study shows how VOI can be used to demonstrate efficient use of limited environmental water to maximise ecological impact and increase transparency when making monitoring or management decisions. More broadly, the study methods will be of interest to any environmental manager who needs to prioritise monitoring and evaluation activities subject to a limited research budget. At a time where researchers and managers are asked to be more accountable for their decision-making, VOI provides a very accessible tool that can speed up the decision of whether to wait and collect more data or act immediately despite uncertainty. Highlights: Value of information (VOI) can evaluate the benefit of collecting more data. We demonstrate a process to engage experts in VOI and increase uptake of results. We use a novel simulation to generate statistical confidence in expert predictions. Only dominant management actions should be considered in multi-objective decisions. Waiting to learn from monitoring has a small but significant expected benefit.